Screen Out Anaemia Among Adolescent Boys as Well! - Gupta, Dheeraj; Pant, Bhawana; Kumari, Ranjeeta; Gupta, Monika (National Journal of Community Medicine, 2013)
Background: Adolescence – a period of transition between childhood and adulthood is a significant period of human growth and maturation. Adolescents represent about a fifth of India’s population. Many studies in recent times have highlighted the high prevalence of anaemia among adolescent girls in India; however, there is limited published literature on prevalence of anaemia among adolescent boys. Aims: To find out the prevalence of anaemia among adolescent (10-19 years) boys and girls in the urban slum of Meerut and to study socio-demographic and other determinants in relation to anaemia. Material and Methods: A Community based cross sectional study was conducted in urban slum, Multan nagar, catchment area of UHTC, Department of Community Medicine, Subharti Medical College, Meerut. A total of 406 (216 females and 190 males) adolescents were included in this study. Haemoglobin estimation was done using Direct Cyanmethaemoglobin method. Statistical analysis were done using Microsoft excel 2007 and Epi info version 3.5.3. Results: The prevalence of anaemia among adolescent males and females was found to be 31.6% and 52.8% respectively. Statistical significant association (p< 0.05) of anaemia among boys were found with type of family, socio-economic status, educational status, academic performance, hand washing before eating main meal, daily frequency of main meals, daily consumption of lemon/sour fruits and BMI. Conclusions: A high prevalence of anaemia was found among adolescent males and females. So there is the need for routine iron supplementation even among adolescent boys.